VO2Max analysis of student futsal athletes - Mutia Ayu Hidayah; Atri Widowati; Anggel Hardi Yanto (Sriwijaya Journal of Sport, 2025)
Research Problems: Physical education aims to improve physical fitness, motor skills, and awareness of a healthy lifestyle. Extracurricular sports, such as futsal, play a role in channelling students' interests while shaping character and social skills. However, the achievement of extracurricular futsal at State Senior High School 1 Muaro Jambi has decreased, allegedly due to low aerobic endurance associated with VO2Max. Research Objectives: The purpose of this study was to analyse the VO₂Max level of student futsal athletes to determine their aerobic capacity. Methods: This research is a quantitative descriptive study with a one-shot-method. Data was collected through the Multistage Fitness Test (MFT) on 27 students who became the research sample. Data analysis was done descriptively quantitative. Results: The results showed that only 1 learner with a percentage (3.7%) had very good VO2Max, 4 learners with a percentage (14.8%) were good, 9 learners with a percentage (33.3%) were moderate, and 13 learners with a percentage (48.1%) were lacking. Conclusion: Most learners have low fitness, which impacts team performance and achievement. This study confirms the importance of a structured training program to improve VO2 max to support optimal performance in competition.